Managing Agency Costs in the face of Challenges and Strategies for Successful Cooperatives A Literature Review - Qonnita, Shaffira; Silfa Mauludina; Siti Fauziah Durotunnisa; Fazar Nuriansyah (LPPM STIE EKA PRASETYA, 2025)
Agency costs are a major challenge in cooperative management, especially in terms of financial efficiency. This study aims to explore the influence of agency costs on the efficiency of cooperative financial management, as well as to identify effective strategies for managing agency costs. The research method used is Systematic Literature Review (SLR) with the PRISMA approach, analyzing 25 selected articles from Google Scholar published in the period 2015-2024. The results of the study show that high agency costs can reduce the efficiency of cooperative financial management, especially due to the lack of transparency and member participation. Some effective strategies that can be implemented include increasing transparency, using technology, restructuring cost efficiency, and education and training for cooperative managers and members. This research provides an important contribution to the development of cooperatives in Indonesia, especially in facing challenges in the Industrial Revolution 4.0 era. However, this study has limitations because it is literature-based and does not involve empirical data. Therefore, further research is recommended to conduct empirical studies to provide a more accurate and contextual picture.